Regulation of Iron Storage by CsrA Supports Exponential Growth of Escherichia coli - Christine Pourciau (American Society for Microbiology, 2019)
ABSTRACT The global regulatory protein CsrA coordinates gene expression in response to physiological cues reflecting cellular stress and nutrition. CsrA binding to the 5′ segments of mRNA targets affects their translation, RNA stability, and/or transcript elongation. Recent studies identified probable mRNA targets of CsrA that are involved in iron uptake and storage in Escherichia coli, suggesting an unexplored role for CsrA in regulating iron homeostasis. Here, we assessed the impact of CsrA on iron-related gene expression, cellular iron, and growth under various iron levels. We investigated five new targets of CsrA regulation, including the genes for 4 ferritin or ferritin-like iron storage proteins (ISPs) and the stress-inducible Fe-S repair protein, SufA. CsrA bound with high affinity and specificity to ftnB, bfr, and dps mRNAs and inhibited their translation, while it modestly activated ftnA expression. Furthermore, CsrA was found to regulate cellular iron levels and support growth by repressing the expression of genes for ISPs, most importantly, ferritin B (FtnB) and bacterioferritin (Bfr). Iron starvation did not substantially affect cellular levels of CsrA or its small RNA (sRNA) antagonists, CsrB and CsrC. csrA disruption led to increased resistance to the lethal effects of H2O2 during exponential growth, consistent with a regulatory role in oxidative stress resistance. We propose that during exponential growth and under minimal stress, CsrA represses the deleterious expression of the ISPs that function under oxidative stress and stationary-phase conditions (FtnB, Bfr, and Dps), thus ensuring that cellular iron is available to processes that are required for growth. IMPORTANCE Iron is an essential micronutrient for nearly all living organisms but is toxic in excess. Consequently, the maintenance of iron homeostasis is a critical biological process, and the genes involved in this function are tightly regulated. Here, we explored a new role for the bacterial RNA binding protein CsrA in the regulation of iron homeostasis. CsrA was shown to be a key regulator of iron storage genes in Escherichia coli, with consequential effects on cellular iron levels and growth. Our findings establish a model in which robust CsrA activity during the exponential phase of growth leads to repression of genes whose products sequester iron or divert it to unnecessary stress response processes. In so doing, CsrA supports E. coli growth under iron-limiting laboratory conditions and may promote fitness in the competitive iron-limited environment of the host large intestine.